2020
DOI: 10.1016/j.sjbs.2020.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Molecular & biochemical analysis of Pro12Ala variant of PPAR-γ2 gene in type 2 diabetes mellitus

Abstract: Diabetes has emerged as a major threat to human life globally. Genomic studies have found a significant link between the Pro12Ala polymorphism of the PPAR-γ2 gene with incidence as well as occurrence of the risk of metabolic syndrome. The present study was aimed at assessing the PPAR-γ2 variant in an Asian Indian cohort of type 2 diabetes patients and its correlation with metabolic parameters. The present case-control study involved 100 type 2 diabetic patients and 100 asymptomatic healthy volunteers enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The prevalence of PPAR-γ2 rs1801282 (Pro12Ala) polymorphism varies across populations. According to genotype frequency, several studies have reported 0% homozygous GG in Asian Indians [31], original South African [32], while in Romanian children and Caucasian adults from Poland the frequency has ranged between 2.7 and 3.7% [33,34]. In teenagers from our region's main ethnic groups, it ranges from 3 to 5%, [27].…”
Section: Discussionmentioning
confidence: 68%
“…The prevalence of PPAR-γ2 rs1801282 (Pro12Ala) polymorphism varies across populations. According to genotype frequency, several studies have reported 0% homozygous GG in Asian Indians [31], original South African [32], while in Romanian children and Caucasian adults from Poland the frequency has ranged between 2.7 and 3.7% [33,34]. In teenagers from our region's main ethnic groups, it ranges from 3 to 5%, [27].…”
Section: Discussionmentioning
confidence: 68%